Study habits and attitudes as correlates of academic achievement in English - Ayson, Lea S. (Animo Repository, 1999)
This study identifies the study habits and attitudes of the Grade VI pupils of EPZA Resettlement Elementary School, School Year 1998-1999. It also determines the degree of correlation between the students' study habits and attitudes and their academic achievement in English.The study utilizes the descriptive research that uses correlational analysis. For statistical treatment, the following were computed:All the raw scores were entered into a Master Sheet organized according to the subjects' name, age, gender and section. The total frequency per item and per area in the Master Sheet were converted into percentages. Then they were ranked from the highest to the lowest frequency percentages. Each item was then analyzed according to converted percents and ranks.The Pearson Product Moment Method of correlation was used to determine the significance of relationship existing between the pupils' study habits and attitudes and their academic achievement in English.The main findings of the study were the following:1. The subjects' study habits and attitudes unde study method, concentration, attitude, motivation and home study conditions were moderate while under school study conditions, it was low. 2. The subjects under study were grouped into homogenous sections according to their previous academic performance. 3. There were significant correlations between the pupils'3.1 study method and academic achievement in English (r=.531,p.01/.05)3.2 concentration and academic achievement in English (r=.471,p.01/.05) 3.3 attitude and academic achievement in English (r=.706,p.01/.05)3.4 motivation and academic achievement in English (r=.602, p.01/.05)3.5 school study conditions and academic achievement in English (r=.149,p.01/.05)3.6 home study conditions and academic achievement in English (r=.676,p.1/.05)4. Attitude was more predictive of academic achievent, followed by home study conditions. The multiple R was .742 and MR squared was .550, which meant that 55 percent of the EPSA Resettlement students' academic achievement was due to attitude and home study conditions.